Ovarian Vein Embolization With N-butyl-2 Cyanoacrylate Glubran-2® for the Treatment of Pelvic Venous Disorder - Gong, Maofeng; He, Xu; Zhao, Boxiang; Kong, Jie; Gu, Jianping; Su, Haobo (Frontiers in Surgery, 2021)
Background: There are few reports in the literature on the use of Glubran-2 for the embolization of ovarian veins in patients with pelvic venous disorder (PeVD). In addition, a consensus on the efficacy and safety of Glubran-2 has not been reached. Purpose: To investigate the safety and efficacy of ovarian vein embolization (OVE) with N-butyl-2 cyanoacrylate (NBCA) Glubran-2 for the treatment of PeVD. Material and Methods: Between January 2013 and January 2020, 21 women (mean age, 43.9 ± 13.3 years) with PeVD who underwent OVE with Glubran-2 were evaluated. Of those patients, ovarian vein or pelvic venous plexus insufficiency was verified by duplex ultrasound and/or multislice computer tomography (MSCT). The symptoms and signs of PeVD included chronic pelvic pain (CPP) (21/21; 100%), dyspareunia (12/21; 57.1%), dysmenorrhea (10/21; 47.6%), and vulvar varices (3/21; 14.3%). The medical data were retrospectively reviewed. Results: Glubran-2 was employed as the sole embolic material in 18 cases (85.7%) and used to perform rescue embolization in 3 cases (14.3%) due to CPP recurrence 1 month after initial embolization using microcoils. Technically successful embolization was achieved using Glubran-2 in all patients. No Glubran-2 related complications were noted. Neither persistent nor recurrent CPP was observed during follow-up, for which the mean was 62 ± 38 months (range, 12–102 months). Clinical efficacy was evaluated, and all patients exhibited complete or slight improvement of CPP after embolization. The visual analog scale (VAS) score significantly decreased from pre-intervention to post-intervention (p < 0.001). Six patients (28.6%) gave birth to healthy babies during follow-up after embolization with Glubran-2. Conclusions: Ovarian vein embolization with Glubran-2 is a feasible and safe treatment for CPP secondary to PeVD. This treatment may represent a potential and attractive alternative when patients desire symptom relief and want to continue reproducing. Larger studies are warranted to confirm the findings of this study.